RETROSPECTIVE STUDY OF PATTERN OF HEAD INJURIES IN ROAD TRAFFIC ACCIDENTS INVOLVING TWO WHEELERS AT BHAVNAGAR REGION-GUJARAT (Journal of Forensic Medicine & Toxicology, 2019)
Introduction: Road traffic accidents (RTA) have been the bane of the modern civilization accounting for considerable loss to the nation. Head injuries are leading causes of death from motorcycle crashes with many deaths occurring despite optimal use of the available treatment facilities. Hence the present study was conducted to know the patterns of head injuries in fatal accidents involving two wheelers. Methods: This retrospective study was conducted from 1stJanuary 2011 to 31st December 2012 at Sir Takhtsinhji General Hospital, Bhavnagar, Gujarat. The present study entirely focuses on the patterns of head injuries in fatal accidents involving two wheelers who were autopsied during this period. A total of 125 cases of deaths due to two wheeleraccidents were reported for the autopsy. Results: Observation shows Riders constituted (64%) and pillion riders (36%).Linear fracture was the commonest pattern of fracture observed in riders (42.50%) and pillion riders (35.55%). Sub-dural haemorrhage was also the commonest intracranial haemorrhage observed in riders (32.50%) and pillion riders (33.33%). Conclusion: In this study it has been observed that for reducing fatalities among victims of two wheeler road traffic accidents, it is essential to study the cause of RTA, which revolves around factors responsible as Human errors, Machine (Vehicle) errors, and environment.
Keywords: Road traffic accidents; Two wheelers; Skullfracture; Haemorrhage